Molecular cloning and in silico studies of physiologically significant trehalase from drosophila melanogaster - Shukla, Ekta; Thorat, Leena; Bhavnani, Varsha; Bendre, Ameya D.; Pal, J. K.; Nath, B. B.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Trehalase, a physiologically important glycosidase is known for its crucial role in insect glycometabolism and stress recovery. The present study describes the molecular cloning of a gene fragment, encoding the catalytically active trehalase from Drosophila melanogaster (DmTre) and its heterologous expression in Escherichia coli. The 1275 bp gene was overexpressed in two different vectors viz., pET28a and pCOLD TF and investigated for variable soluble expression, purification and activity of the recombinant enzyme with optimum pH and temperature of enzyme as 6 and 55 degrees C, respectively. The sequence was characterized in silico by subjecting it to homology search, multiple sequence alignment and phylogenetic tree construction revealing its identity to other trehalases which belong to glycoside hydrolase family 37. The deduced amino acid sequence and modeled 3D structure of DmTre possessed all features of trehalase superfamily, including signature motifs and catalytic domain. The active site pocket of recombinant DmTre was compared with the crystal structure of E. coli trehalase identifying Glu424 and Asp226 as the putative catalytic residues. Additionally, enzyme-substrate docking suggests possible involvement of other residues in the catalysis along with Asp226. The present study holds significance in understanding the structural aspects of Drosophila trehalase in spite of unavailabilty of eukaryotic trehalase crystal structure. (C) 2016 Elsevier B.V. All rights reserved.

Analysis of Kunitz inhibitors from plants for comprehensive structural and functional insights - Bendre, Ameya D.; Ramasamy, Sureshkumar; Suresh, C. G. (International Journal of Biological Macromolecules, 2018)
Legume Kunitz type trypsin inhibitor (KTI) family is one of the most versatile families of proteins. A typical KTI features a single peptide folded in beta-trefoil manner, with the molecular weight about 20-22 kDa and two disulphide bonds. The members are known to inhibit a wide range of serpins proteases at the same time many of them possess unique features. Copaifera langsdoiffii Trypsin inhibitor (CTI) has a beta-trefoil fold made up of two non-covalently bound polypeptide chains with only a single disulfide bridge. Delonix regia Trypsin inhibitor (DrTI) has one amino acid insertion between P1 and P2 of the reactive site distorting its conformation. Bauhinia bauhinioides Cruzipain inhibitor (BbCI) has a conservative beta-trefoil fold but lacks disulfide bonds. Such subtle differences in structures make Kunitz inhibitors different from other inhibitor families. Most of the studies on these inhibitors are focused towards their proposed role in defense from insect pests and wounding but their exact physiological role in nature is still uncharted. Thus, it would be very interesting to closely analyze the structural details of these inhibitors in order to ascertain their biological role and other fascinating applications. (C) 2018 Elsevier B.V. All rights reserved.

Cloning and characterization of trehalase: a conserved glycosidase from oriental midge, Chironomus ramosus - Shukla, Ekta; Thorat, Leena; Bendre, Ameya D.; Jadhav, Santosh; Pal, Jayanta K.; Nath, Bimalendu B.; Gaikwad, Sushama M. (3 Biotech, 2018)
Insect trehalase is a multiferous enzyme, crucial for normal physiological functions as well as under stress conditions. In this report, we present a fundamental study of the trehalase gene segment (1587 bp) from Chironomus ramosus (CrTre) encoding for 529 amino acids, using appropriate bioinformatics tools. C. ramosus, a tropical midge is an emerging animal model to investigate the consequences of environmental stresses. We observed that CrTre belongs to GH family 37 in the CAZy database and possess 57-92% identity to dipteran trehalases. In silico characterization provided information regarding the structural, functional and evolutionary aspects of midge trehalase. In the phylogenetic tree, CrTre clustered with the soluble dipteran trehalases. Moreover, domain functional characterization of the deduced protein sequence by InterProScan (IPR001661), ProSite (PS00927 and PS00928) and Pfam (PF01204) indicated presence of highly conserved signature motifs which are important for the identification of trehalase superfamily. Furthermore, the instability index of CrTre was predicted to be < 40 suggesting its in vivo stability while, the high aliphatic index indicated towards its thermal stability (index value 71-81). The modelled 3D tertiary structure of CrTre depicts a (alpha/alpha)(6) barrel toroidal core. The catalytic domain of the enzyme comprised Glu424 and Asp226 as the putative active site residues. Interestingly, the conserved motifs were observed to be formed by the flexible loopy regions in the tertiary structure. This study revealed essential sequence features of the midge trehalase and offers better insights into the structural aspects of this enzyme which can be correlated with its function.
Keywords: Conserved motifs; Homology modelling; Midges; Secondary structure; trehalose

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin

Functional stability and structural transitions of a kunitz trypsin inhibitor from chickpea (CaTI2) - Bendre, Ameya D.; Shukla, Ekta; Ramasamy, Sureshkumar (Protein Journal, 2020)
Enzymes are important tools for various applications. We have studied structural transitions and functional stability of a Kunitz trypsin inhibitor from Chickpea (CaTI2), a potent insect gut-protease inhibitor, under different stress conditions like non-neutral pH, elevated temperature and co-solvent concentrations. CaTI2 was cloned and expressed in an eukaryotic systemP. pastorisand was investigated for conformational transitions using circular dichroism spectroscopy, differential scanning fluorimetry and activity assay. Native CaTI2 has a sheet dominant structure with 40% beta sheets and possess a single tryptophan residue situated in the hydrophobic core of the enzyme. The recombinant inhibitor maintained its maximum activity under alkaline pH with its secondary structure intact between pH 6-10. CaTI2 was observed to be thermally stable up to 55 degrees C with aT(m) of 61.3 degrees C above which the protein unfolds. On treating with chemical denaturant (urea), the CaTI2 lost its inhibitory potential and native conformation beyond 2 M urea concentration. Moreover, the protein unfolded at lower temperatures as the concentration of denaturant increased, suggesting more complex structural changes. Further, the stability of the inhibitor was found to be directly proportional to the solvent polarity. The data, herein offers significant information of inhibitor stability and activity which could be exploited for its further development into an effective pesticide. [GRAPHICS] .
Keywords: Chickpea; Circular dichroism spectroscopy; Differential scanning fluorimetry; Functional stability; Kunitz trypsin inhibitor